"A estranha felicidade da velhice" na poesia de Mario Quintana e de Carlos Drummond de Andrade - Ribas, Nathalia Sabino (2008)
The present research analyzes how the human aging process is approached by the lyric self in Mario Quintana and Carlos Drummond de Andrade poetry. Its objectives are: to study the procedures and performances used in the selected poems to recuperate that theme; to discover, in such poems, the relations established between the social status attributed to the elderly and the images they develop about themselves; to identify, in the poetic universe, the physical and emotional characterization of the elderly, verifying whether the lyric selves evoke memories of their childhood during their old years, and also how they live love in that phase of their lives. In order to accomplish that, the analytic comparative method is employed, together with literary anthropology as studied by Wolfgang Iser, a theorist who acknowledges the peculiarities of the literary text while, at the same time, recognizes its connection with reality. The analysis allows asserting that, for the lyric selves in the works by Quintana and Drummond, growing old means to know how to become another, observing the world and oneself beyond the masks imposed by society and time. That knowledge, once acquired, is what preserves in the lyric selves the ability to dream, although there is not much time left, and the fears and uncertainties invade them in the last phase of their lives